2013
DOI: 10.1088/1612-2011/10/6/065606
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair in bacterial cultures and plasmid DNA exposed to infrared laser for treatment of pain

Abstract: Biostimulation of tissues by low intensity lasers has been described on a photobiological basis and clinical protocols are recommended for treatment of various diseases, but their effects on DNA are controversial. The objective of this work was to evaluate effects of low intensity infrared laser exposure on survival and bacterial filamentation in Escherichia coli cultures, and induction of DNA lesions in bacterial plasmids. In E. coli cultures and plasmids exposed to an infrared laser at fluences used to treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 49 publications
3
24
1
Order By: Relevance
“…Due to these properties, T 4 endonuclease V protects patients with xeroderma pigmentosum against skin cancer ( 32 ). Plasmid DNA exposed to low-intensity red and infrared lasers did not show any alterations in electrophoretic profile in agarose gels, suggesting absence of detectable single- or double-strand DNA breaks, as previous studies have demonstrated ( 19 , 20 ). In addition, the plasmids did not show any alteration in their electrophoretic profile after incubation with T 4 endonuclease V, suggesting that red and infrared laser lights did not induce DNA lesions targeted by this enzyme, at least under the laser irradiation conditions used in this study.…”
Section: Methodssupporting
confidence: 81%
See 2 more Smart Citations
“…Due to these properties, T 4 endonuclease V protects patients with xeroderma pigmentosum against skin cancer ( 32 ). Plasmid DNA exposed to low-intensity red and infrared lasers did not show any alterations in electrophoretic profile in agarose gels, suggesting absence of detectable single- or double-strand DNA breaks, as previous studies have demonstrated ( 19 , 20 ). In addition, the plasmids did not show any alteration in their electrophoretic profile after incubation with T 4 endonuclease V, suggesting that red and infrared laser lights did not induce DNA lesions targeted by this enzyme, at least under the laser irradiation conditions used in this study.…”
Section: Methodssupporting
confidence: 81%
“…Previous studies demonstrated a biostimulatory effect in prokaryote ( 10 ) and eukaryote ( 30 ) cells. Recently, we observed this effect in cell cultures proficient in DNA repair mechanisms, but not in an E. coli strain deficient in repair of oxidative DNA lesions ( 20 ). No studies have demonstrated biostimulation that was dependent on laser beam power.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Induction of filamentation phenotype is reported in E. coli cells irradiated with the low-level lasers, as in those with mutations in genes related to DNA repair pathways for oxidative damages. 15,16,20 However, the filamentation assay performed in these studies did not allow for evaluating what happened with cells which do not present this phenotype. To attempt this need, area and perimeter were measured in mutant E. coli cells in SOS functions (AB2463 and AB2494) and compared to E. coli wild type cells (AB1157).…”
Section: Discussionmentioning
confidence: 99%
“…Biological effects caused by free radicals from laser light are controversial and possible adverse effects on cells and data about DNA damage after laser exposure have been reported in eukaryotic [10][11][12][13][14] and prokaryotic cells [15][16][17][18][19][20][21][22][23] , at different powers, wavelengths and fluences. In addition, as regard to DNA, a variety of studies have suggested that exposure to red and near infrared low-intensity lasers could induce adaptation or DNA damage at a sub-lethal level.…”
Section: Introductionmentioning
confidence: 99%